Collectors Classics Art Forum : The selection of Wim Reiff, Maastricht, The Netherlands, Volume II, 2002. - Artschwager, Richard; Bömmels, Peter; Cabot, Roberto; Dickhoff, Wilfried; Egenhofer, Sebastian; Gohr, Siegfried; Lynch, Florence; Reiff, Wim; Steenbergen, Renée; Steinweg, Marcus (Maastricht : Collectors Classics Art Forum, 2002)
Het alternatief voor veilinghuizen
Allotey, Fatima ; Appel, Karel ; Artschwager, Richard ; Baechler, Donald ; Balkenhol, Stephan ; Barcelo, Miguel ; Barfuss, Ina ; Barry, Robert ; Baselitz, Georg ; Bastings, Maurice ; Baumgarten, Lothar ; Ben Ali, Rachid ; Berghs, Antoine ; Beuys, Joseph ; Bijl, Guillaume ; Blais, Jean-Charles ; Blake, Peter ; Boltanski, Christian ; Bömmels, Peter ; Bourgeois, Louise ; Brandl, Herbert ; Brus, Günter ; Brus, Johannes ; Buetti, Daniele ; Buthe, Michael ; Byars, James Lee ; Cabot, Roberto ; Chaissac, Gaston ; Chia, Sandro ; Clemente, Francesco ; Coenen, Jo ; Condo, George ; Constant ; Copley, William ; Dahn, Walter ; Daniels, René ; Dobrev, Ivan ; Dokoupil, Jiri Georg ; van Dongen, Kees ; Droese, Felix ; Droese, Irmel ; Dumas, Marlene ; Dwurnik, Edward ; Elders, Fons ; Fabre, Jan ; Fasioli, Paola & Giancarlo ; Fautrier, Jean ; Ferraris, Carlo ; Finkenauer, Sabine ; Förg, Gunther ; Frese, René ; Garcia, Sevilla Ferràn ; de Goey, Marijke ; Gomes, Fernanda ; Groumellec, Loic Le ; Grygar, Milan ; Guilleminot, Marie ; Hänningen, Nanna ; Hartung, Hans ; Heppener, Robert ; Herbin, Auguste ; Herold, Georg ; Hockney, David ; Höfer, Candida ; van Hoffs, Katharina ; Holzer, Jenny ; Huber, Felix Stephan ; Imbach, Samuel ; Immendorff, Jörg ; Israels, Isaac ; Jongkind, Johan Barthold ; Kabakov, Ilya ; Kappl, Franco ; Katase, Kazuo ; Katz, Alex ; Katz, Benjamin ; Kelley, Mike ; Kiecol, Hubert ; Kiefer, Anselm ; Kim, Wonsook ; Kippenberger, Martin ; Kirchner, Ernst Ludwig ; Kirkeby, Per ; Knap, Jan ; Knoebel, Imi ; Koberling, Bernd ; Koekkoek, Barend Cornelis ; Korteland, Richard ; Kosuth, Joseph ; van Landuyt, Colette ; Lange, Thomas ; Lavier, Bertrand ; Levine, Sherrie ; LeWitt, Sol ; De Maria, Nicola ; McCollum, Allan ; Melgaard, Bjarne ; Merz, Gerhard ; etc.
biografie
Engels
boek